The Influence of Marketing Strategies on the Sale of Kobelco Heavy Equipment at PT. X Constructions Machinery Indonesia Branch Pekanbaru - Rita Zahara (Greenation Research & Yayasan Global Resarch National, 2024)
This research was conducted at PT X Contructions Machinery Indonesia at the Pekanbaru branch which is located at Jalan Arifin Ahmad number 111 Pekanbaru, from February 2023 to September 2023. This research is motivated by the sales of Kobelco heavy equipment at PT X Contructions Machinery Indonesia, Pekanbaru branch from 2018 to 2022 still has not reached the target set while the sales target trend every year continues to increase and also the higher level of competition for heavy equipment and other brands in Pekanbaru city today. For this reason, promotional activities are a very important means for PT X Contructions Machinery Indonesia at the Pekanbaru branch to optimize heavy equipment sales in achieving sales targets. The population in this study were consumers of PT X Contructions Machinery Indonesia at the Pekanbaru branch, with the number of samples taken randomly, namely 61 respondents using the Slovin method. The analysis method used is quantitative analysis, namely multiple regression analysis. From the results of the analysis carried out, the regression equation is obtained. The publicity variable has the greatest influence on purchasing decisions. Hypothesis testing using the t test which shows that all independent variables have a significant effect on the dependent variable or purchase decision. Then the F test shows that the variables X1, X2, X3 and X4 together have an effect on the Purchasing Decision variable. The Adjuster R Square figure shows that changes in sales should be determined by the independent variable, namely the promotion variable, while the rest is determined by other factors not observed in this study.